Amendment to Term of Office of Constitutional Court Judges in Indonesia: Reasons, Implications, and Improvement - Idul Rishan; Sri Hastuti Puspitasari; Siti Ruhama Mardhatillah (Fakultas Hukum Universitas Muhammadiyah Magelang, 2022)
After the amendment to the Constitutional Court Law, constitutional court judges would be dismissed honorably when they attain the age of 70 (seventy) years old. Problem arises, where the transitional provisions of the third amendment to the Constitutional Court Law are not applicable prospectively but retroactively. Hence, the implementation of the amendment to the term of office of constitutional court judges also brings an impact on the incumbent constitutional judges in the Constitutional Court. This study had three objectives. First, to identify the underlying reasons (ratio-legis) for the amendment to the term of office of constitutional court judges to the maximum age limit of 70 years. Second, to analyze the implications of arranging a maximum age limit of 70 years for the position of constitutional court judges. Third, to recommend alternative arrangements for the term of office of constitutional court judges in Indonesia. This was a legal doctrinal research with a qualitative analysis. The results showed that (1) the reasons for the amendment to the term of office of constitutional court judges are due to the open legal policy, globalization and efforts to build the pro-majoritarian power in the Constitutional Court. (2) This amendment brings implications, i.e., the distortion of judicial independence, conflicts of interest and a declined public trust. (3) Improvements can be made by revising the transitional provisions and trying other alternatives by arranging the term of office of the judges through the constitution.